2020
DOI: 10.1111/fcp.12604
|View full text |Cite
|
Sign up to set email alerts
|

Metformin potentiates the chemotherapeutic effects of doxorubicin on 2‐amino‐1‐methyl‐6‐phenylimidazo[4,5b] pyridine‐induced Mammary Carcinoma in rats

Abstract: This study was carried out to evaluate the antitumor activity of Metformin (Met) and its impending utility to potentiate the chemotherapeutic action of doxorubicin on 2‐amino‐1‐methyl‐6‐phenylimidazo[4,5b]pyridine (PhIP)‐induced rat mammary carcinogenesis. Female Sprague –Dawley (SD) rats were divided into seven groups (n = 15 each). Mammary carcinogenesis was induced by the administration of PhIP at a dose of 75 mg/kg by gavage. Met treatment was 2 mg/ml in drinking water for 26 weeks started after the last P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Similarly, repurposing of Met for cancer treatment was suggested due to its direct effect on the AMPK pathway in tumor cells [32] and other metabolic-related mechanisms [33]. Despite the limited availability of clinical data supporting the use of statins or Met as monotherapy for cancer management, numerous investigations have evidenced their enhancing role with traditional chemotherapy [17]. Also, their beneficial combined effect was reported in many human disorders (exemplified in Table 4 [34][35][36][37][38][39][40][41][42][43][44][45]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, repurposing of Met for cancer treatment was suggested due to its direct effect on the AMPK pathway in tumor cells [32] and other metabolic-related mechanisms [33]. Despite the limited availability of clinical data supporting the use of statins or Met as monotherapy for cancer management, numerous investigations have evidenced their enhancing role with traditional chemotherapy [17]. Also, their beneficial combined effect was reported in many human disorders (exemplified in Table 4 [34][35][36][37][38][39][40][41][42][43][44][45]).…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of Met was attributed to both metabolic and epigenetic modulation of the cancer cells and the involvement of several signaling pathways like AMPK, AKT, and mTOR and activation of P53 [14, 15]. In the same manner, we previously found that the antiproliferative effect of Met was attributed to the dysregulation of AMPK and the associated oxidative stress in the mammary carcinoma rat model [16] and the drug enhanced the anticancer effect of Doxorubicin as well [17].…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, MF protects only normal cells, without preventing damage to cancer cells [13][14][15]. It also shows synergism with some chemotherapeutic agents [110][111][112]. A review [14] is devoted to these properties of MF, considering the mechanisms of its action as a radioprotector with an anticancer effect.…”
Section: Metformin In Cancer Therapymentioning
confidence: 99%
“…An increase in tumor oxygenation is believed to be a possible radiosensitizing mechanism of MF [14,115], due to the reduction of oxygen consumption by mitochondria [13], and the induction of the oxygen effect [116]. It has been noted that MF affects even cancer stem cells that are chemoresistant and radioresistant, improving the prognosis of tumor treatment and reducing relapses [60,112].…”
Section: Metformin In Cancer Therapymentioning
confidence: 99%
“…It was used previously combined with resveratrol (Osman et al, 2012), superoxide dismutase (Villani et al, 1992), or other agents like amifostine, which is a broad spectrum cytoprotectant against radio and chemotherapy-related toxicities in vitro and in vivo while maintaining antitumor activity (Dragojevic-Simic et al, 2013). We have recently coupled Doxorubicin with metformin, a natural biguanide that is a type 2 anti-diabetes prescription, to reduce its side effects and boost its effectiveness against breast cancers in vivo (Salim et al, 2021).…”
Section: The Efficiency Of Amygdalin and Doxorubicin Combination On H...mentioning
confidence: 99%